Mekanisme Penggantian Kepala Desa - Hasibuan, Siti Aisyah; Gunawan, Syafri (Jurnal El-Thawalib, 2022)
Implementation of the Regulation of the Minister of Home Affairs Number 66 of 2017 Article 8 Concerning the Mechanism of Replacement of Village Heads in Matondang Village, Ulu Barumun District, Padang Lawas Regency". The replacement of the village head is a stage that is carried out when the term of office of the village head has ended, whether it is the end of the term of office because the village head resigns, dies, requests himself or is dismissed. The formulation of the problem in this study is how to implement the Minister of Home Affairs Regulation number 66 of 2017 article 8 regarding the replacement of village heads in Matondang village, Ulu Barumun district, Padang Lawas district?, and what are the factors that hinder the implementation of the Minister of Home Affairs Regulation number 66 of 2017 article 8 regarding the replacement of the village head in Matondang village, Ulu Barumun sub-district, Padang Lawas district?. This research is a type of qualitative research, Qualitative research emphasizes efforts to answer research questions through formal argumentative ways of thinking. This type of research is research in the form of field studies or field research.In this study, the researchers found that the mechanism for replacing the village head in Matondang Village, Ulu Barumun sub-district, Padang Lawas district, was an important thing that must be done in the village government so that there was no vacancy in the village head position. The community considers that the replacement of the village head in Matondang Village, Ulu Barumun District, Padang Lawas Regency has been in accordance with the applicable stages or mechanisms, but the majority of people consider it not in accordance with the Implementation of the Minister of Home Affairs Regulation No.